2022
DOI: 10.3390/foods11060864
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-Based Approach for Coffee Beverage Improvement in the Context of Processing, Brewing Methods, and Quality Attributes

Abstract: Coffee is a worldwide beverage of increasing consumption, owing to its unique flavor and several health benefits. Metabolites of coffee are numerous and could be classified on various bases, of which some are endogenous to coffee seeds, i.e., alkaloids, diterpenes, sugars, and amino acids, while others are generated during coffee processing, for example during roasting and brewing, such as furans, pyrazines, and melanoidins. As a beverage, it provides various distinct flavors, i.e., sourness, bitterness, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 110 publications
0
16
0
Order By: Relevance
“…A multiplexed approach in food metabolomics based on analytical techniques, either indirect as LC/MS or direct, including nuclear magnetic resonance (NMR) and ultraviolet-visible spectrometry (UV/Vis), has been increasingly reported in food authentication and quality control [ 16 , 17 ]. Particularly, LC/MS is well suited for the profiling of phytoextracts, especially after the recent development of UPLC/MS, owing to its improved peak resolution and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…A multiplexed approach in food metabolomics based on analytical techniques, either indirect as LC/MS or direct, including nuclear magnetic resonance (NMR) and ultraviolet-visible spectrometry (UV/Vis), has been increasingly reported in food authentication and quality control [ 16 , 17 ]. Particularly, LC/MS is well suited for the profiling of phytoextracts, especially after the recent development of UPLC/MS, owing to its improved peak resolution and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…NMR-based metabolomics study is recognized as a direct analytical platform and always imparts more credibility to identification results owing to its strong elucidation power aside from being quantitative (qNMR) providing a readout out of metabolite abundance in extracts [ 20 , 43 ]. A total of 16 metabolites were identified based on 1D- and 2D-NMR analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, chemometrics and multivariate data analyses (MVA) are potential candidates for such purposes, including unsupervised tools such as principal component analysis (PCA) and supervised orthogonal projections to latent structures discriminant analysis (OPLS-DA) [ 15 ]. Therefore, metabolomics-based profiling, fingerprinting, and processing of herbal products have been well documented meanwhile for quality assessment purposes, where various direct and indirect analytical platforms are used to target certain classes of phytoconstituents [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that different brewing methods affect not only the chemical composition but also the aroma [ 36 , 63 ]. Metabolite variations are also influenced by temperature as in hot or cold brews [ 86 ], brewing time, or the size of ground solids [ 45 , 58 ]. In contrast to studies by Rothwell et al [ 36 ], studies by Kim et al [ 33 ] indicated that the composition of bioactive compounds was dependent upon roasting rather than brewing methods.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that differences in coffee metabolites and caffeine levels [ 36 , 37 ] are influenced by their geographic origins or environment [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], post-harvest processing [ 30 , 33 , 45 , 46 , 47 , 48 ], instant versus fresh ground coffees [ 49 , 50 ], degrees of roasting [ 33 , 51 , 52 , 53 ], and/or types of brewing methods [ 31 , 33 , 36 , 49 , 54 , 55 , 56 ]. Different coffee metabolites not only impart flavors [ 38 , 57 , 58 ] or aromas [ 59 , 60 , 61 , 62 , 63 ], but also determine therapeutic impact by influencing antioxidant potential [ 34 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%